Properties of Whole Saliva and Dental Plaque in Relation to 40-Month Consumption of Chewing Gums Containing Xylitol, Sorbitol or Sucrose - Mäkinen, K.K.; Chen, C.-Y.; Mäkinen, P.-L.; Bennett, C.A.; Isokangas, P.J.; Isotupa, K.P.; Pape, K.R., Jr (Caries research, 1996)
Samples of whole saliva and dental plaque were collected from initially 10-year old subjects who participated in a 40-month cohort study investigating the effect of chewing gum usage on caries rates. The subjects represented nine cohorts of which one did not receive gum, while in eight cohorts the subjects received gum containing either xylitol, sorbitol, their mixtures, or sucrose as bulk sweeteners, the maximum sweetener consumption in the form of gums being up to 10.7 g/day, used in 3–5 daily chewing episodes. Gum usage had no significant effect on the levels of salivary protein, IgA, α-amylase, peroxidase, lysozyme, SCN- and buffer capacity. At the endpoint, the group that received 100% xylitol pellet-shaped gum five times/day, had significantly lower levels of sucrase (p < 0.05) and free sialic acid (p < 0.001) in whole saliva than at baseline. This group showed significantly (p < 0.05) smaller plaque index scores at two cross-sectional measurements, and exhibited the lowest log 10 counts of salivary lactobacilli at endpoint than most other groups. The salivary levels of peptidase(s) (oligopeptidase B-like enzymes) hydrolyzing Nα-benzoyl-DL-arginyl-p-nitroaniline were significantly (p < 0.05) or almost significantly lower in groups which received 100% xylitol pellet gums. All groups exhibited obviously an aging-related increase of salivary mutans streptococcus scores, except the above xylitol group in which the mean scores did not change.